2021
DOI: 10.18502/pbr.v7i2.7360
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine Ameliorated Mitochondrial Oxidative Damage Induced by Sub-chronic Exposure to Cadmium in Mice Kidney

Abstract: Background:Cadmium is a heavy metal that can cause various injuries in the body, including nephrotoxicity. L-Arginine is a metal chelator that can prevent oxidative damage caused by oxygen free radicals. Objectives:This study aimed to investigate the effect of L-arginine in inhibiting mitochondrial toxicity induced by subchronic cadmium exposure in the kidney of male mice. Methods: A total of 42 male mice were randomly divided into six groups (n=6): control (normal saline), cadmium (2 mg/kg), cadmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The present study has demonstrated that administration of exogenous L-arginine in combination with ascorbic acid is beneficial in potassium bromate-induced organ damage in rats. Our results agree with those of previous studies which reported that doses of ascorbic acid or L-arginine between 500 and 1000 mg/kg body weight restored induced alterations in biochemical indices of kidney function in rodents, and that histological aberrations induced in renal tissues were also ameliorated (Kandhare et al, 2015;Shaki et al, 2021). The probable mechanism of action of L-arginine is its antioxidative effect elicited by direct chemical interaction with superoxide anion (Liang et al, 2018, Li et al, 2022.…”
Section: Discussionsupporting
confidence: 92%
“…The present study has demonstrated that administration of exogenous L-arginine in combination with ascorbic acid is beneficial in potassium bromate-induced organ damage in rats. Our results agree with those of previous studies which reported that doses of ascorbic acid or L-arginine between 500 and 1000 mg/kg body weight restored induced alterations in biochemical indices of kidney function in rodents, and that histological aberrations induced in renal tissues were also ameliorated (Kandhare et al, 2015;Shaki et al, 2021). The probable mechanism of action of L-arginine is its antioxidative effect elicited by direct chemical interaction with superoxide anion (Liang et al, 2018, Li et al, 2022.…”
Section: Discussionsupporting
confidence: 92%
“…N-acetylcysteine + Orn treatment may have reduced Cd-induced liver DNA damage. Antioxidant properties of Orn (especially betaine), PPE and NAC may have prevented oxidative DNA damage in the liver tissue [ 25 , 26 , 36 , 41 , 48 , 63 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ornipural (1 mL/kg) treatments on some biomarkers in liver tissue toxicity of Cd (mg/kg) in rats (Mean ± SEM) The liver MDA levels decreased in concomitant administration of NAC and NAC + Orn with Cd (P˂0.05, Table 1). Ornipural has antioxidant ingredients such as L-arginine, betaine, and methionine, which positively affect antioxidant enzymes [41,63]. N-acetylcysteine increases the level of intracellular antioxidant enzymes such as GSH and has scavenging effects on oxidative radicals [48].…”
Section: Table 1 the Effect Pomegranate Peel Extract (Ppe) (Mg/kg) An...mentioning
confidence: 99%
See 1 more Smart Citation
“…MDA is the end product of the membrane lipid peroxidation produced by action of free radicals (Shokrzadeh et al 2015;Shaki et al 2021). ROS are products of normal metabolism in body (Teow et al 2007;Iqbal et al 2012) that is excessively generated by a prolonged hyperglycemia (Taile et al 2020).…”
mentioning
confidence: 99%